2002
DOI: 10.1051/0004-6361:20021230
|View full text |Cite
|
Sign up to set email alerts
|

An $\vec{XMM}$-$\vec{Newton}$ observation of the Lagoon Nebula and the very young open cluster NGC 6530

Abstract: Abstract. We report the results of an XMM-Newton observation of the Lagoon Nebula (M 8). Our EPIC images of this region reveal a cluster of point sources, most of which have optical counterparts inside the very young open cluster NGC 6530. The bulk of these X-ray sources are probably associated with low and intermediate mass pre-main sequence stars. One of the sources experienced a flare-like increase of its X-ray flux making it the second brightest source in M 8 after the O4 star 9 Sgr. The X-ray spectra of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 41 publications
10
50
1
Order By: Relevance
“…For many years, this star was presumed to be a single source. The situation only changed when its X-ray properties as well as episodic variations of some optical line profiles over long timescales were interpreted as signatures of a long-period (eight to nine years) eccentric double-lined spectroscopic binary (SB2) system (Rauw et al 2002a, hereafter Paper I; Rauw et al 2005). This scenario was confirmed when we obtained a first orbital solution of 9 Sgr (Rauw et al 2012, hereafter Paper II), and when phase-locked variations of the radio flux at 2 cm were reported by Blomme & Volpi (2014, hereafter Paper III).…”
Section: Postdoctoral Researcher Frs-fnrs (Belgium) Senior Research mentioning
confidence: 99%
“…For many years, this star was presumed to be a single source. The situation only changed when its X-ray properties as well as episodic variations of some optical line profiles over long timescales were interpreted as signatures of a long-period (eight to nine years) eccentric double-lined spectroscopic binary (SB2) system (Rauw et al 2002a, hereafter Paper I; Rauw et al 2005). This scenario was confirmed when we obtained a first orbital solution of 9 Sgr (Rauw et al 2012, hereafter Paper II), and when phase-locked variations of the radio flux at 2 cm were reported by Blomme & Volpi (2014, hereafter Paper III).…”
Section: Postdoctoral Researcher Frs-fnrs (Belgium) Senior Research mentioning
confidence: 99%
“…In particular, following up on pioneering ROSAT observations, intermediate to distant clouds have been covered by Chandra: the Orion nebula (Garmire et al 2000;Feigelson et al 2002Feigelson et al , 2003Flaccomio et al 2003), part of the Rosette nebula and molecular cloud, together with M17 (Townsley et al 2003;Wang et al 2008Wang et al , 2009); Mon R2 (Kohno et al 2002); RCW38 (Wolk et al 2002); M16 (Linsky et al 2007), and by XMMNewton: M8 (Rauw et al 2002); Carina (Albacete Colombo et al 2003); Vela OB2 (Jeffries et al 2009); Orion (López-Santiago & Caballero 2008); and others. Up to thousands of point X-ray sources per cloud are detected, almost all identified with young stars, down to the brown dwarf regime.…”
Section: Search For Young Stars Based On X-ray Datamentioning
confidence: 99%
“…Loktin et al (1997) 1800 11.25 Sung et al (2000) 560-711 8.75-9.26 Loktin & Beshenov (2001) low mass stars are expected to be still in the pre-main sequence phase, as already found in Sung et al (2000) from photometric data down to the limiting magnitude V ∼ 17. 119 X-ray point sources in the Lagoon Nebula region have been recently detected by Rauw et al (2002) in a 20 ks XMM-Newton observation; they found that most of the X-ray sources are associated with pre-main sequence stars of low and intermediate mass. However, a larger list of point sources in the same region, with a much better spatial resolution, has recently been obtained by Damiani et al (2004), using Chandra ACIS-I X-ray data.…”
Section: Introductionmentioning
confidence: 99%